2011
DOI: 10.1007/s10165-011-0460-5
|View full text |Cite
|
Sign up to set email alerts
|

Primary lack of efficacy of infliximab therapy for rheumatoid arthritis: pharmacokinetic characterization and assessment of switching to tocilizumab

Abstract: To characterize primary failure to infliximab and determine the efficacy of switching to tocilizumab in patients with rheumatoid arthritis (RA), we examined 24 RA patients who had started on infliximab therapy (3 mg/kg) as their first biological agent. Nine of the 24 patients were found to be primary nonresponders, defined as patients who had never achieved a 20% clinical improvement according to the American College of Rheumatology criteria (ACR20) during induction therapy. The remaining 15 patients had achie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Antibody positivity was associated with lower or undetectable circulating infliximab levels [21,24,26,27,30,32,[34][35][36][37][39][40][41], and a lower likelihood of disease control or remission [21,24,27,28,[35][36][37][38]42,43,46,52]. However, in a prospective study of patients with UC, undetectable infliximab concentrations were associated with less favorable clinical outcomes irrespective of antibody status [41], suggesting that antibody formation may not be the sole mechanism underlying the loss of efficacy.…”
Section: Infliximab Studiesmentioning
confidence: 73%
“…Antibody positivity was associated with lower or undetectable circulating infliximab levels [21,24,26,27,30,32,[34][35][36][37][39][40][41], and a lower likelihood of disease control or remission [21,24,27,28,[35][36][37][38]42,43,46,52]. However, in a prospective study of patients with UC, undetectable infliximab concentrations were associated with less favorable clinical outcomes irrespective of antibody status [41], suggesting that antibody formation may not be the sole mechanism underlying the loss of efficacy.…”
Section: Infliximab Studiesmentioning
confidence: 73%
“…The recommendation is to use TCZ in combination with MTX [ 1 ]. The usage of TCZ as second line bDMARD after failure of TNFi which was shown to be an effective treatment option by several RCTs [ 15 17 ] is common in Germany. A recent study showed that in short-term use (6-months follow-up) TCZ was equally effective in biologic-naïve patients and patients with prior bDMARD failures [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is postulated to cause cell lysis via antibody-dependent cell-mediated cytotoxicity or complement activation17, 18 ) .…”
Section: Introductionmentioning
confidence: 99%